Dampak Perancangan Sistem Informasi Reservasi Hotel Berbasis Website Di Hotel Meganita - Agustina, Alya; Aulia, Widya; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of implementing a website-based hotel reservation information system at Hotel Meganita on operational efficiency and service quality. The research method employed is Research and Development (R&D) using the Waterfall model. System testing was conducted using black-box testing and User Acceptance Test (UAT). The results indicate that the implementation of the website-based reservation system increased room booking process efficiency by 87.5%, reduced reservation recording errors from 15 cases to 2 cases per month, and improved customer satisfaction levels from 72% to 94%. In addition, the system provides 24/7 reservation access, thereby expanding customer reach. Therefore, the website-based reservation information system has a significant positive impact on the operational performance of Hotel Meganita.